2012
DOI: 10.1523/jneurosci.4697-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

GABA Site Agonist Gaboxadol Induces Addiction-Predicting Persistent Changes in Ventral Tegmental Area Dopamine Neurons But Is Not Rewarding in Mice or Baboons

Abstract: In behavioral experiments, we found neither acute reinforcement in intravenous selfadministration sessions with THIP at relevant doses using a yoked control paradigm in mice nor in baboons using a standard paradigm for assessing drug abuse liability; nor was any place preference found after conditioning sessions with various doses of THIP but rather a persistent aversion in 6 mg/kg THIP-conditioned mice. In summary, we found that activation of extrasynaptic ␦-subunit-containing GABA A receptors leads to glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 85 publications
4
77
0
Order By: Relevance
“…We first searched for slightly sedative doses of GAN after acute injections to locate the closest match to our previous study with THIP (Vashchinkina et al, 2012) that has a full agonistic profile at extrasynaptic GABA A receptors (Storustovu and Ebert, 2006). We found that GAN 30 mg/ kg produced a transient reduction in locomotor activity of young mice, whereas a 10 mg/kg dose did not affect activity (Figure 1a and b).…”
Section: Effects Of Gan On Locomotor Activity Of Micementioning
confidence: 75%
See 4 more Smart Citations
“…We first searched for slightly sedative doses of GAN after acute injections to locate the closest match to our previous study with THIP (Vashchinkina et al, 2012) that has a full agonistic profile at extrasynaptic GABA A receptors (Storustovu and Ebert, 2006). We found that GAN 30 mg/ kg produced a transient reduction in locomotor activity of young mice, whereas a 10 mg/kg dose did not affect activity (Figure 1a and b).…”
Section: Effects Of Gan On Locomotor Activity Of Micementioning
confidence: 75%
“…a-Amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) and Nmethyl-D-aspartate (NMDA) receptor EPSCs were induced by stimulating glutamatergic afferents at 0.1 kHz frequency using a bipolar stimulus electrode (Vashchinkina et al, 2012). Neurons were clamped at þ 40 mV in the presence of GABA A receptor blocker picrotoxin (100 mM), and EPSCs were recorded for 10 min before and after the application of NMDA receptor blocker D-( À )-2-amino-5-phosphonopentanoic acid (AP5 50 mM).…”
Section: Electrophysiological Experimentsmentioning
confidence: 99%
See 3 more Smart Citations